Global governance and local peace: accountability and performance in i nternational peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Bu rundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountabl e, locally adaptive – International organizations in peacebuilding–glo bally accountable, locally constrained – Bilateral development donors– accountable for global targets, not local change